Evaluation of Patients Undergoing Spinal Cord Stimulation Using the e-Health Tool - Hanzade Aybüke Ünal; Ersin Sönmez; Hüseyin Emre Arıkan; Ahmet Başarı; Güngör Enver Özgencil; İbrahim Aşık (Ankara Üniversitesi Tıp Fakültesi Mecmuas, 2025)
Objectives: The aim of the study is to evaluate patients undergoing spinal cord stimulation (SCS) using an online decision support system (SCS e-health tool). Materials and Methods: In this study, data of patients who underwent SCS between 2005 and 2023 at the Department of Algology, Ankara University Faculty of Medicine, were retrospectively analyzed. The clinical characteristics of the patients were assessed using an e-health tool scoring system proposed by the panel and presented online. Furthermore, the alignment of the implanted SCS devices with the recommendations of this scoring system was evaluated. Results: It was determined that the median SCS appropriateness score for the 117 patients who underwent SCS implantation was 7, and only 3 patients had the SCS removed during the trial period. All the patients who underwent SCS implantation in our study met the eligibility criteria for SCS according to the e-health tool algorithm. Conclusion: We observed a much lower rate of SCS removal during the trial period compared to the literature. We believe this is attributable to the multidisciplinary evaluation conducted at our hospital by highly competent specialists from various fields who assess patients for SCS suitability.